Estudos de expressão em genes potencialmente envolvidos no processo reprodutivo em Anastrepha obliqua (Diptera, Tephritidae) - Nakamura, Aline Minali (2014)
The majority of species in the genus Anastrepha is endemic to the Neotropics and many are of great economic importance because they inflict great damage to several different fruit crops. Brazil has low insertion in international markets because of the demand for quality products with no pesticide residues, which force the improvement of control techniques. Thus, an alternative to insect pests control is the Sterile Insect Technique (SIT), which reduces the pest population by mass release of sterile insects. However, sterilization by radiation has many side effects, reducing the competitiveness of released males relative to wild males. For this reason, different strategies have been used, such as the production of transgenic individuals not only in order to sterility but also increasing the vitality presented by these males compared to wild males. To accomplish that, an important approach could be the study of genes involved in the reproductive process. In this work, we selected nine candidate genes for expression studies of our transcriptome data, which have the potential of being involved in the reproductive process in Anastrepha because they belong to gene families that have already been associated to the reproductive process, and showed differential expression between the contrast of virgin and post-mating of transcriptome data in Anastrepha flies. Since no qPCR study has been done to date in Anastrepha, we tested several reference genes for normalization of expression data. The genes Rpl18, Rps17 and Ef1a were deemed suitable and used here to standardize studies of expression between life stages of A. obliqua. The qPCR gene expression analysis revealed interesting gene expression patterns for AttA, Obp56a and Obp99c, which increases the potential of these genes being involved in the reproductive process. Obp56a showed a higher expression in virgin females in contrast to postmating, whereas AttA and Obp99c showed higher expression in male in contrast to females, which may be interesting for genetic control techniques. We applied the RNAi silencing technique with AttA and Obp99c, aiming to generate information about the participation of these genes in reproduction. Thus, our results pointed for three candidate genes that could be interesting for population control techniques, with potential of being involved in the reproductive process, which stimulates further researches in Anastrepha obliqua.